Pendidikan Karakter sebagai Strategi dalam Pencegahan Perilaku Bullying di SMP - Maryani Maryani; Rina Inayah; Reza Mauldy Raharja (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research discusses the importance of educational character in preventing bullying in educational units. Character education is an educational system whose learning can influence everyone, especially education to demonstrate moral values, ethics and civic attitudes towards oneself and others. However, character education is currently a challenge in its implementation, especially with the rise of problems such as verbal and non-verbal bullying among students. Moreover, now the problem of bullying does not only occur in ordinary schools, but can also occur in international schools. One of the factors is a lack of ability to control behavior, an inability to manage emotions which ultimately triggers a desire for revenge in order to adapt to the environment. The strategies needed to overcome bullying include teacher sensitivity towards students, creating a safe atmosphere, forming an anti-bullying team, and conducting outreach about the dangers of bullying.